PENGARUH IKLIM ORGANISASI DAN ETOS KERJA TERHADAP KINERJA KEPALA MADRASAH TSANAWIYAH NEGERI DI PROPINSI SUMATERA BARAT - FAUQA NURI ICHSAN (Jurnal Manajemen Pendidikan, 2011)
The objective of research is to find out influences of the Organization Climate and Work Ethic toward the Principal’s performance of MTsN in province West Sumatera. This research used as a sample of 88 Principals of MTsN, and 20 Principals of MTsN for testing, and selected based on a simple random technique (Simple Random Sampling). The study was a causal survey using path analysis. Technique data collecting was using the instrument in the form of questionnaire. This instrument is calibrated with the test item validity and reliability coefficients. To test the validity of using Pearson Product Moment correlation, while the reliability coefficient is calculated using the formula of Alpha Cronbach. The results showed that, 1) there is a direct influences of organization climate toward the Principal’s performance, 2) there is a direct influences of work ethic toward the Principal’s performance, 3) there is a direct influences of organization climate toward work ethic.The implication of this research is an effort in improving the performance of Principal’s of MTsN can be done through organization climate and work ethic.